Oestrogen Receptor Alpha and Progesterone Receptor in Uterus and Ovaries on Different Days of The Oestrus Cycle in Hyperthyroid Rats - Bozoglu, Halil; Karaca, Turan (Asian Journal of Medical Sciences, 2014)
Background: The present study evaluated, in different oestrus cycle phases, the oestrogen receptor alpha (ERα) and progesterone receptor (PgR) in rates with hyperthyroid ovaries and uterus. Materials and Methods: Sixty-four adult female wistar albino rats were used. Animals were randomly separated into eight different groups, four of which constituted the control group and the other four of which were the actual experimental group. Hyperthyroidism was induced by daily s.c. injection of L-thyroxine (L-T4, 250 µg/kg) for 21 days. Results: Hyperthyroidism induced decreased plasma TSH levels and increased plasma free T4 levels (P < 0.001). In addition, it increased plasma oestrogen levels in all cycle phases, and plasma progesterone levels increased in different cycle phases, excluding the oestrus phase, in rats (P < 0.01). By the end of the experiment, ERα percentages were decreased in oestrus days in uterine luminal epithelium; however, ERα percentages were increased in metoestrus phases in hyperthyroid rats. ERα was elevated in proestrus, metoestrus and dioestrus phases in the corpus luteum, and hyperthyroidism also increased ERα percentages in theca folliculi. In uterine luminal epithelium, the hyperthyroidism group showed higher expressions of PgR (P < 0.05) in oestrus and metoestrus phases and decreased oestrus phase compared to control rats. Conclusions: As a result, we conclude that both the levels of plasma estrogen and progesterone as well as the differences in the distributions of relevant receptors in ovarian and uterus tissues have an impact on female infertility due to hyperthyroidism. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11816 Asian Journal of Medical Sciences Vol.6(4) 2015 14-20